The Growth of China and India in World Trade : Opportunity or Threat for Latin America and the Caribbean? - Lederman, Daniel; Olarreaga, Marcelo; Soloaga, Isidro (World Bank, Washington, DC, 2012)
This paper studies the relationship between the growth of China and India in world merchandise trade and Latin American and Caribbean commercial flows from two perspectives. First, the authors focus on the opportunity that China and India's markets have offered Latin American and Caribbean exporters during 2000-2004. Second, empirical analyses examine the partial correlation between Chinese and Indian bilateral trade flows and Latin American and Caribbean trade with third markets. Both analyses rely on the gravity model of international trade. Econometric estimations that control for the systematic correlation between expected bilateral trade volumes and the size of their regression errors, as well as importer and exporter fixed effects and year effects, provide consistent estimates of the relevant parameters for different groups of countries in Latin America and the Caribbean. Results suggest that the growth of the two Asian markets has produced large opportunities for Latin American and Caribbean exporters, which nevertheless have not been fully exploited. The evidence concerning the effects of Chinese and Indian trade with third markets is not robust, but there is little evidence of negative effects on Latin American and Caribbean exports of non-fuel merchandise. In general, China's and to a large extent India's growing presence in world trade has been good news for Latin America and the Caribbean, but some of the potential benefits remain unexploited.